Filgrastim versus TBO‐filgrastim to reduce the duration of neutropenia after autologous hematopoietic stem cell transplantation: TBO, or not TBO, that is the question. (22nd October 2015) - Trifilio, Steven; Zhou, Zheng; Galvin, John; Fong, Jessica L.; Monreal, Joanne; Mehta, Jayesh
Abstract: After a hospital‐wide formulary change resulted in the replacement of filgrastim with TBO‐filgrastim for all on‐ and off‐label indications, we performed a retrospective comparison of patients with myeloma receiving 200 mg/m 2 melphalan with autologous hematopoietic stem cell transplantation to see whether the type of growth factor used post‐transplant made a difference. One hundred and eighty‐two consecutive patients with myeloma were studied, 91 receiving filgrastim immediately prior to the change and 91 receiving TBO‐filgrastim afterward. The CD34 + cell dose was comparable, as were other characteristics. Although the overall time to neutrophil recovery was similar for both groups, early engraftment (≤12 d) occurred more often (p = 0.05), and late engraftment (≥14 d) less often (p = 0.09) in filgrastim‐treated patients. The number of documented infections was significantly less in the TBO‐filgrastim group. Day 100 mortality and hospital stay were similar for the two groups. These data indicate that there is no material difference between filgrastim and TBO‐filgrastim in this clinical setting.